Dysregulation of complement system in HELLP syndrome - Shi Chen; Zheng Li; Yingdong He; Qian Chen (Hypertension in Pregnancy, 2021)
Objective To investigate the expression of complement system’s activation factors in patients with HELLP syndrome. Methods A case–control study was performed. Sixteen HELLP syndrome patients, 32 severe preeclampsia patients, and 48 normal pregnancy women were involved in this studyELISA was used to test C1q, C4d, MBL, Bb, C3a, C5a, sC5b-9, s-Endoglin, and sflt-1 in the plasma. Results The levels of C5a (P < 0.01) and sC5b-9 (P = 0.014) in HELLP syndrome were higher than those in severe preeclampsia patients. Conclusions The abnormal activation of the complement system is more significant in the pathogenesis of HELLP syndrome than in severe preeclampsia.